Wypełnianie pola literackiego. O zmianie w recepcji literatury bułgarskiej w Polsce - Pytlak, Magdalena (Przekłady Literatur Słowiańskich, 2020)
This article is a commentary on the changing reception of Bulgarian literature in Poland in 2018 and 2019. Using Pierre Bourdieu’s theory of the literary field, it shows the mechanisms of recognition by the main actors within the field, including publishers, media, and others. The analysis focuses on three books translated from Bulgarian to Polish in 2018: Sofia Berlin, by Plamen Doynov, and Koniec minotaurów (The End of the Minotaurs) and Fizyka smutku (The Physics of Sorrow), both by Georgi Gospodinov. The analysis is made on two levels. One is generic, owing to the fact that two of the three books are poetry. The second is authorial, as two of the books are by the same author.